Bicyclol Attenuates Liver Inflammation Induced by Infection of Hepatitis C Virus via Repressing ROS-Mediated Activation of MAPK/NF-κB Signaling Pathway - Li, Hu; Li, Jian-Rui; Huang, Meng-Hao; Chen, Jin-Hua; Lv, Xiao-Qin; Zou, Li-Li; Tan, Jia-Li; Dong, Biao; Peng, Zong-Gen; Jiang, Jian-Dong (Frontiers in Pharmacology, 2018)
Treatment with direct-acting antivirals (DAAs) cures most patients infected with hepatitis C virus (HCV) in the real world. However, some patients, especially those with underlying advanced liver disease, have a limited reduction of liver injury after achieving a sustained viral response (SVR). Bicyclol was widely used in clinic for the treatment of a variety of liver injuries but with an unknown mechanism for the treatment of hepatitis C. We investigated the anti-inflammatory effects and mechanisms of bicyclol in HCV-infected hepatocytes and further confirmed the putative results in mouse hepatitis model induced by the co-injection of polyinosinic-polycytidylic acid [poly (I:C)] and D-galactosamine (D-GalN). The results showed that the activation of nuclear factor kappa B (NF-κB) and subsequent increase of inflammatory factors were directly induced by HCV infection and were persistent after clearance of the virus in Huh7.5 cells. Bicyclol decreased the activation of NF-κB and the levels of inflammatory factors in HCV-infected hepatocytes by inhibiting the activation of the ROS-MAPKs-NF-κB pathway, and the effect was synergistic with DAAs in HCV-infected hepatocytes. Bicyclol attenuated the ROS/MAPKs/NF-κB axis via recovering mitochondrial function without a dependence on dihydronicotinamide adenine dinucleotide phosphate oxidase and superoxide dismutases. The anti-inflammatory effects and mechanism of bicyclol were verified in mouse hepatitis induced by the co-injection of poly(I:C)/D-GalN. Conclusion: Bicyclol directly ameliorates the chronic inflammation caused by HCV infection and might be used with DAAs or after DAA therapy for ultimately curing chronic hepatitis C.